2005
DOI: 10.1186/1472-6882-5-4
|View full text |Cite
|
Sign up to set email alerts
|

Use of biological based therapy in patients with cardiovascular diseases in a university-hospital in New York City

Abstract: Background: The use of complementary and alternative products including Biological Based Therapy (BBT) has increased among patients with various medical illnesses and conditions. The studies assessing the prevalence of BBT use among patients with cardiovascular diseases are limited. Therefore, an evaluation of BBT in this patient population would be beneficial. This was a survey designed to determine the effects of demographics on the use of Biological Based Therapy (BBT) in patients with cardiovascular diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
65
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(67 citation statements)
references
References 38 publications
1
65
1
Order By: Relevance
“…the inclusion of non-UK studies, and identified 10 new papers, as noted above. [185][186][187][188][189][190][191][192][193][194] Five further studies were identified by unstructured searching. [195][196][197][198][199] In total, 20 studies were included.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…the inclusion of non-UK studies, and identified 10 new papers, as noted above. [185][186][187][188][189][190][191][192][193][194] Five further studies were identified by unstructured searching. [195][196][197][198][199] In total, 20 studies were included.…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies were conducted in the USA; 185,186,189,192,[194][195][196][197]199 one of these was colocated in Puerto Rico; 185 five were conducted in the UK, [167][168][169][170][171] three in Australia, 190,193,198 two in Canada 187,188 and one in Germany. 191 Thirteen studies evaluated adults' views concerning the taking of vitamins and minerals, 169,185,187,[189][190][191][192][193][195][196][197][198][199] five studies considered aspirin or NSAIDs, [168][169][170][171]194 two folic acid 167,185 and two dietary supplements generally. 186,188 Only four studies explored the views of participants who had either a cancer diagnosis 186,197,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In several trials, total cholesterol levels, HDL, LDL-cholesterol, triglycerides, apolipoprotein A and B and lipoprotein A were not significantly improved with nutraceutical or vitamin-mineral treatment [65]. A trend was noted in favor of nutraceutical therapy with reduced total cholesterol TC level >240 mg/dL, LDL > 155 mg/dL TC levels (significant only for >240 mg/dL), and Body Mass Index > 25 kg/m 2 was associated with better improvements [66].…”
Section: Lipid Metabolism and Fatty Acid Modifiers As Basis Of Cvd Anmentioning
confidence: 99%